1999
DOI: 10.1507/endocrj.46.643
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Parathyroid Hormone-Related Peptide and Cytokine Levels in Synovial Fluid of Elderly Rheumatoid Arthritis and Osteoarthritis.

Abstract: Abstract.We simultaneously measured the concentrations of parathyroid hormone related peptide (PTHrP) and cytokines in synovial fluid (SF) to clarify the relationship between PTHrP and cytokine network in the SF of elderly patients with arthritis.SF was collected from knee joints of five RA patients aged 66± 11 years old and nine osteoarthritis (OA) patients aged 80±9 years old. PTHrP in SF was measured by enzyme-linked immunosorbent assay (ELISA), whereas tumor necrosis factor-a (TNF-a), interleukin-1 j3 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 18 publications
3
21
0
2
Order By: Relevance
“…The strong correlation we found between synovial fluid IL-18 and TNFα is consistent with these reports. The concentration of synovial fluid TNFα we found in our subjects was similar to previous reports for OA synovial fluid and approximately sixfold lower than has been reported for RA (34,35). Although we found a strong correlation of TNFα with uric acid concentration and OA severity, the lower levels of TNFα when compared with RA, along with the correspondingly lower IL-18, suggest a less acute inflammatory process driven by IL-18 as part of an innate immune response.…”
Section: Discussionsupporting
confidence: 88%
“…The strong correlation we found between synovial fluid IL-18 and TNFα is consistent with these reports. The concentration of synovial fluid TNFα we found in our subjects was similar to previous reports for OA synovial fluid and approximately sixfold lower than has been reported for RA (34,35). Although we found a strong correlation of TNFα with uric acid concentration and OA severity, the lower levels of TNFα when compared with RA, along with the correspondingly lower IL-18, suggest a less acute inflammatory process driven by IL-18 as part of an innate immune response.…”
Section: Discussionsupporting
confidence: 88%
“…In pathological states accompanied by bone loss such as osteoporosis, periodontal disease and rheu-matoid arthritis, recent attention has been focused on cytokines including interleukin-1 (IL-1) generated in the bone microenvironment that may be responsible for stimulating osteoclastic bone resorption [10,11]. Several studies suggested that increased IL-1 production by human peripheral blood mononuclear cells (PBMCs) is responsible for development of osteoporosis [12,13].…”
Section: Osteoclastsmentioning
confidence: 99%
“…More recently, PTHrP has also been identified as a member of the cascade of cytokines produced in prodigious amounts by the rheumatoid synovium (5,6). As with other cytokines, PTHrP is expressed by synoviocytes, the primary cell comprising the tumor-like rheumatoid synovium (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…As with other cytokines, PTHrP is expressed by synoviocytes, the primary cell comprising the tumor-like rheumatoid synovium (5)(6)(7)(8)(9). TNF␣ and IL-␤, 2 key inflammatory cytokines in RA, induce synoviocyte PTHrP expression, and PTHrP, in turn, induces synoviocyte secretion of IL-6 (5).…”
mentioning
confidence: 99%